Patient, hospital, and local health system characteristics associated with the use of observation stays in veterans health administration hospitals, 2005 to 2012. Issue 36 (September 2016) - Wright, Brad; O'Shea, Amy M.J.; Glasgow, Justin M.; Ayyagari, Padmaja; Vaughan-Sarrazin, Mary
Abstract : Abstract: Recent studies have documented that a significant increase in the use of observation stays along with extensive variation in patterns of use across hospitals. The objective of this longitudinal observational study was to examine the extent to which patient, hospital, and local health system characteristics explain variation in observation stay rates across Veterans Health Administration (VHA) hospitals. Our data came from years 2005 to 2012 of the nationwide VHA Medical SAS inpatient and enrollment files, American Hospital Association Survey, and Area Health Resource File. We used these data to estimate linear regression models of hospitals' observation stay rates as a function of hospital, patient, and local health system characteristics, while controlling for time trends and Veterans Integrated Service Network level fixed effects. We found that observation stay rates are inversely related to hospital bed size and that hospitals with a greater proportion of younger or rural patients have higher observation stay rates. Observation stay rates were nearly 15 percentage points higher in 2012 than 2005. Although we identify several characteristics associated with variation in VHA hospital observation stay rates, many factors remain unmeasured.